Strategi Peningkatan Kinerja Sumber Daya Manusia pada UMKM Melalui Implementasi Kontrol Suhu Berbasis Arduino Uno pada Oven - Syabria Kurniawati; Mira Yona; Habibudin Nasution (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
In the era of Industry 5.0, MSMEs must adopt smarter workforce management system to boost production and efficiency in response to technological advancements. This study examines how MSMEs can leverage appropriate (automation) technologi ti implement smart workforce management principles. This foucuses on an Arduino Uno-based automatic temperature control system as the main technology deployed in one of the suitable technologies utilized in Mr. Sugeng's MSME's brownie production oven. The research employed observation, interviews and documentation as data collection methods. Implamentation results demonstrate that using an automated temperature control system could increase work efficiency by 30% as it eliminates manual oven monitoring, there by freeing operators to focus on other tasks. As a result, daily production ooutput rose from 650-800 pcs to 850-1050 pcs. Beyond productivity gains, this thecnology also improved the operator’s digital skill, reduced thei physical workload, and facilitated data-driven decision-making. These finding illustrate that Smart Workforce idea can enable more flexible, accurate, and productive work patterns when automated technology and human talents are combined. Overall, this implementation shows that appropriate technology not only improves operational performance, but it also supports human resource development and boosts MSMEs' competitiveness amid digital transformation.